STUDENTS’ READINESS FOR MASSIVE OPEN ONLINE COURSES (MOOCS) IN LATVIA - Birzina, Rita; Cedere, Dagnija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
MOOCs have gained popularity increasingly more and more with their open online approach and mass engagement. They could play an important role in higher education. But the question remains whether students are ready for it. The aim of the study was to find out what students' understanding of online learning was and to what extent they were prepared for MOOCs. A research question was raised: there is a relationship among technical competencies, socio-communication competencies, self-efficacy, self-directedness and MOOCs readiness. The survey-monkey's electronic platform was used for data extraction. Open-ended questions were asked on the 4-point Likert scale. According to the research question raised, items were grouped in 5 blocks. Two hundred and forty-seven (247) students participated in the study from different Latvian universities. The descriptive statistics (Mean, Standard Deviation), Mann-Whitney U tests were used in data processing in order to compare the opinions of full-time and part-time students, Kruskal Wallis test for finding out the differences among the opinions of students who are of different age about the engagement in MOOCs. The factor analysis was used for determination main dimensions of the MOOCs readiness – socio-communication competencies, self-efficacy, self-directness, and technical competencies. Spearman's correlation was used for identifying the correlations among these factors. The results obtained showed that there was a relationship among student’s self-directness and socio-communication competencies, and self-efficacy, and readiness for MOOCs, although most students prefer face to face learning.